UPAYA MENINGKATKAN HASIL BELAJAR IPA MATERI TUMBUHAN DAN SUMBER KEHIDUPAN DI BUMI MELALUI MODEL PEMBELAJARAN PROBLEM BASED LEARNING (PBL) SISWA KELAS V SDN KELUN - Fiorennica; Hartini; Siti Juwarmini (STKIP Subang, 2024)
The research conducted aims to determine the improvement of science learning outcomes on the material of plants and sources of life on earth using the problem based learning (PBL) learning model for fifth grade students. This study uses the Classroom Action Research (CAR) approach of the Kemmic MC Taggart model consisting of planning, implementation, observation, and reflection. Information is collected through observation, testing, documentation, and interviews. The research was conducted on fifth grade students of SDN Kelun with a total of 29 respondents. Based on the results of the study, student learning outcomes in cycle I have not reached completion with an average value of student learning outcomes of 50,35% and the percentage of students who have completed their learning is 47,35%. While student learning outcomes in cycle II have reached completion with an average value of student learning outcomes of 75,50% and the percentage of students who have completed their learning is 84%.